Exploring the relationship between ambient sulfur dioxide and semen quality parameters: A systematic review and meta-analysis - Seyed Sobhan Bahreiny; Mojtaba Aghaei; Mohammad Reza Dabbagh; Hamid Ghorbani; Moslem Javidan; Reza Mohammadpour Fard (Asian Pacific Journal of Reproduction)
Objective: To investigate the relationship between ambient sulfur dioxide (SO2) exposure and semen quality parameters. Methods: A systematic literature search was conducted to identify relevant studies investigating the association between SO2 exposure and semen quality parameters. This search encompassed the timeframe from January 2000 to May 2023 and included electronic databases such as Web of Science, Google Scholar, PubMed, Cochrane, and Scopus. Pooled effect estimates with 95% confidence intervals (CI) were calculated using percent changes (PC). The meta-analysis included seven studies with 6 711 participants and 15 087 semen samples. Results: The results revealed a significant negative association between ambient SO2 exposure and certain semen quality parameters. In particular, SO2 exposure was associated with a significant decrease in progressive motility (PC=0.032; 95% CI: -0.063 to -0.001; P=0.044) and sperm concentration (PC = -0.020; 95% CI: -0.036 to -0.005; P=0.012). However, no statistically significant associations were observed for total sperm count (PC = -0.038; 95% CI: -0.079 to 0.003; P=0.070), seminal fluid volume (PC = -0.009; 95% CI: -0.048 to -0.030; P=0.662) and sperm motility (PC = -0.17; 95% CI: -0.363 to 0.022; P=0.830). In addition, the results of the subgroup analysis revealed specific variables that were associated with the decrease in relevant sperm parameters. Conclusions: This systematic review and meta-analysis provides compelling evidence supporting a consistent negative association between exposure to ambient SO2 and semen quality parameters.